Vacíos legales en el Código Orgánico Integral Penal, respecto de las lesiones causadas por accidentes de tránsito que produzcan en la víctima un daño, enfermedad o incapacidad que no exceda de tres días - Elizalde Maldonado, Jonathan Xavier (2015)
his legal research work entitled "loopholes IN INTEGRAL ORGANIC PENAL CODE, WITH REGARD TO INJURY TRAFFIC ACCIDENT VICTIM TO OCCUR IN INJURY, ILLNESS OR DISABILITY NO MORE THAN THREE DAYS," his study is essential due to the personal integrity of the victims of traffic accidents whose injury, illness or disability not exceed three days, they can not be penalized because there is no criminal rule that repress this illegal act, leaving unpunished and violating the rights delas victims they are guaranteed the Supreme Law pro. In analyzing the Code of Criminal Integral observe any rule which does not provide that guarantee rights of people with minor injuries when they are three days of disability in traffic accidents, therefore inobserva the right to an effective remedy and right to legal certainty. The theoretical, legal and doctrinaire collection, case studies, conducting surveys and interviews allowed me to get recognized criteria very clear and precise basis of literature, which contributed to the verification of the objectives and the testing of the hypothesis